Asymmetrical proliferative pattern loss linked to cyclin D1 overexpression during malignant transformation of the lip epithelium. (13th June 2016) - Garcia, N.G.; González‐Moles, M.A.; Ruiz‐Ávila, I.; Bravo, M.; Ramos‐García, P.; Minicucci, E.M.; Domingues, M.A.C.; Oliveira, D.T.
Abstract: Background: There is inadequate knowledge on the involvement of oncogenic mechanisms linked to the cyclin (CCND1) gene in lip squamous cell carcinoma (LSCC). Objective: The aim of this study was to analyse the implication of cyclin D1 in the malignant transformation of lip lesions. Methods: We immunohistochemically studied 45 actinic cheilitis cases (15 mild dysplasia, 15 moderate dysplasia, 15 severe dysplasia/carcinoma in situ), 30 LSCC cases with adjacent non‐tumour epithelium and 15 normal oral epithelium samples for detection of cyclin D1, β‐catenin and Ki‐67. Results: C yclin D1 and Ki‐67 expressions were significantly increased in the basal layer of premalignant epithelia and peripheral layers of tumour nests vs . controls. Premalignant epithelia had lost their asymmetrical proliferative pattern. Conclusion: Lip carcinogenesis was associated with loss of the asymmetrical proliferative pattern, a preventive mechanism against lip oncogenesis, and with cyclin D1 overexpression.